3D Mirrored Object Selection for Occluded Objects in Virtual Environments - Lee, Joong-Jae; Park, Jung-Min (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
There is an increasing demand for the manipulation of virtual objects in 3D virtual reality (VR) space, which begins with the user selecting a desired object. Existing selection methods aim to provide an intuitive and natural experience that minimizes user fatigue. Although typical ray-casting methods are effective when objects in the virtual space are sparsely or evenly placed, the selection becomes challenging when these objects are smaller or farther away, particularly when they overlap. In this study, we propose a method to address these challenges via an effective selection process. Based on 3D mirroring, the proposed method provides a new interaction metaphor that allows for a more efficient selection of occluded virtual objects. We conduct systematic experiments with 21 subjects and use various levels of target visibility determined by object size, spatial density, and degrees of occlusion. The results indicate that, in occluded 3D environments, the proposed 3D mirrored selection process outperforms traditional gaze-supported selection processes and offers better user satisfaction.
Keywords: DENSE